2013
DOI: 10.1057/jma.2013.5
|View full text |Cite
|
Sign up to set email alerts
|

Brand relations and life course: Why old consumers love their brands

Abstract: Dirk Sikkelis a Statistician and Market Researcher. He has worked for different market research agencies and as a professor in methodology. During the last 12 years, he has specialized in marketing to older consumers. Currently, he is a Professor at the University of Amsterdam in the department of communication sciences and has his own company Sixtat.Correspondence: Dirk Sikkel, Sixtat, Schout van Eijklaan 98, Leidschendam, 2262 XV, The Netherlands E-mail: d.sikkel@sixtat.nl ABSTRACT The relationship between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…Cole et al [2008] have highlighted some drivers that affect the brand preferences that vary with age: a habit mechanism that develops with age and decreases in willingness to innovate. Similar results were obtained by Sikkel [2013], who showed that among elder customers a decreased tolerance to ambiguity, consistent with low cognitive-affective complexity results in a higher need for longer, well-established relationship with the brand and affects its associations, as the consumers were seeking for brands with a long history and presence on the market.…”
Section: Older Customer Behaviors and Brand Associationssupporting
confidence: 82%
“…Cole et al [2008] have highlighted some drivers that affect the brand preferences that vary with age: a habit mechanism that develops with age and decreases in willingness to innovate. Similar results were obtained by Sikkel [2013], who showed that among elder customers a decreased tolerance to ambiguity, consistent with low cognitive-affective complexity results in a higher need for longer, well-established relationship with the brand and affects its associations, as the consumers were seeking for brands with a long history and presence on the market.…”
Section: Older Customer Behaviors and Brand Associationssupporting
confidence: 82%
“…Current marketing and brand positioning techniques often confuse consumers ( Walsh and Yamin, 2005 ; Wang and Shukla, 2013 ). Research that identifies the sensitivity of an individual to brand ambiguity and to the type and intensity of information cues that eliminate brand ambiguity and aid consumers in distinguishing one brand from another is needed ( Sikkel, 2013 ). Such research would have both scholarly and applied value.…”
Section: Opportunities For Research Concerning Ambiguity Tolerancementioning
confidence: 99%
“…For example, according to Sikkel (2013), the association between age and brand relationship strengthens, implying that businesses should signal to older consumers that they want to serve them throughout their life journey while staying within their comfort zone. While the value of human interactions is emphasized, businesses must ensure that the issue of consumer privacy is addressed effectively.…”
Section: Extent Of Crm's Effect In Telecommunication's Customer Reten...mentioning
confidence: 99%